Stages of oculomotor dysfunctions confirms the model of axonal spread of pTDP-43 pathology in amyotrophic lateral sclerosis. Issue 3 (March 2016) - Gorges, M.; Müller, H.-P.; Lulé, D.; Del Tredici, K.; Brettschneider, J.; Keller, J.; Ludolph, A.C.; Kassubek, J.; Pinkhardt, E.H.
Abstract : Objective: To see whether the sequential corticofugal spreading of pTDP-43 pathology in amyotrophic lateral sclerosis (ALS) (Brettschneider et al., Ann Neurol 2013) permit the categorization of eye movement disturbances in a corresponding oculomotor staging scheme. Methods: Saccadic and smooth pursuit eye movements were video-oculographically recorded from 68 ALS patients and 31 matched healthy controls in order to compute parameters for executive oculomotor functions and brainstem oculomotor circuitry performance. Results: Thirty patients had no oculomotor abnormalities compared to controls, all other presented a broad spectrum of impaired eye movement control including increased anti- and delayed saccades errors, a high prevalence of saccadic intrusions, gaze-palsy and a cerebellar type of smooth pursuit disturbance. Oculomotor deficits manifested sequentially witch permits a categorization of two stages: Stage 1, exclusively executive dysfunctions, and Stage 2, executive deficits plus impaired, genuine' oculomotor control such as gaze-palsy or impaired pre-cereballary circuits. Conclusions: Impaired executive eye movements appear as the initial manifestation, followed by disturbed infratentorial oculomotor control pathways. Key message: Alterations in eye movement control in ALS follow a sequential pattern and may serve as a technical marker of the corticofugal axonal spread of the disease.